The Different Narrations in the Ancestry of the Ṣufriyya Group - Altalafha, Zaid (Dirasat: Human and Social Sciences, 2020)
The study aims at identifying the ancestry of the Ṣufriyya group, principles, opinions, and ideas that they believed in. In addition to revealing the causes of the group breaking apart, classifying the most important and most prominent splinter groups, its relation with the other khawarij groups, and with the Umayyad state, especially that Sufriyya had a prominent role in the demise of the state of the Umayyad.